Brand reputation and consumer behaviour: what is the impact of consumer behaviour on brand reputational crisis? - Sajdeh, Dhruv (2013)
Brand crisis has been known to greatly lower the sales of products of a company, often at a global level. However, several brands have also emerged as strong as ever from such crisis. This study sought to evaluate the relationship between corporate reputation, brand crisis, crisis response and consumer loyalty. It relied on a consumer survey and a managerial survey to note the similarities and differences in the perception of consumer behaviour and expectation during times of brand crisis. Key findings were that brand reputation played a major role in retaining loyal customers during a crisis. It was also found that adequate mitigation that met consumer expectations was crucial in retaining a substantial part of the consumer base. Poor or the lack of response could have dire long term consequences for the brand.